A meta-proteomics approach using autopsy material from the pre-antibiotic era from patients with untreated pulmonary tuberculosis to identify proteins present in early lesions of post-primary tuberculosis - Beatrice Normann; Syeda Mariam Riaz; Lisbet Sviland; Tehmina Mustafa; Even Birkeland (PLoS ONE, 2026)
Primary TB and post-primary TB (PPTB) are different disease entities. PPTB occurs only in humans, and no animal model mimics the actual pathology of PPTB. Information on the immune pathogenesis of PPTB is lacking due to the scarcity of untreated human material. In the early stages of PPTB, lesions can either progress or regress. Mycobacterial proteins present in these early lesions are vital to identifying targets for future development of better vaccines and therapeutics. Using proteomics, we aimed to establish a methodology to identify mycobacterial proteins expressed in lesions of human PPTB from the archival formalin-fixed and paraffin-embedded lung tissue from 1937−1941. Five untreated TB patients with a total of eleven samples were used. Micro-dissected tissue from six early and five necrotic lesions were processed for proteomics. Using a mass spectrometry and multiplexing tandem-mass-tag (TMT) approach, a total of 3531 Homo sapiens and 110 bacterial proteins were identified and quantified. Four M. tuberculosis proteins; mIHF (accession p71658), groEL2 (accession P9WPE7), RV2971 (accession P9WQA5), cycA (accession O33203), and 1 Mycobacterium avium protein hup (accession A0A0H3A054) were identified. Comparison of early lesions with necrotic lesions showed significantly more RV2971 proteins expressed in early lesions, and mIHF expressed in necrotic lesions (Log2 fold change necrotic – early; 1.401 & −0.581 respectively). In conclusion, we established the methodology and proof of principle for detecting M. tuberculosis proteins in PPTB lesions at different stages of the disease. We identified four M. tuberculosis proteins, two showing significant differential expression in early and necrotic lesions.